PLAUR as a Potential Biomarker Associated with Immune Infiltration in Bladder Urothelial Carcinoma - Liu M (Dove Medical Press, 2021)
Mulin Liu,1 Siyi Chen,2 Aihui Zhang,2 Qin Zheng,2 Juan Fu3 1Department of Clinical Laboratory, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning Province, 116011, People’s Republic of China; 2Department of Biochemistry and Molecular Biology, College of Basic Medical Science, Dalian Medical University, Dalian, Liaoning Province, 116044, People’s Republic of China; 3Department of Obstetrics and Gynecology, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning Province, 116011, People’s Republic of ChinaCorrespondence: Qin ZhengDepartment of Biochemistry and Molecular Biology, Liaoning Provincial Core Laboratory of Glycobiology and Glycoengineering, College of Basic Medical Science, Dalian Medical University, 9 West Section, Lvshun South Road, Dalian, Liaoning Province, 116044, People’s Republic of ChinaTel/ Fax +86 411-86110308Email zhengqin90@126.comJuan FuDepartment of Obstetrics and Gynecology, The First Affiliated Hospital of Dalian Medical University, No. 222 Zhongshan Road, Dalian, Liaoning Province, 116011, People’s Republic of ChinaTel +86 411-83635963 ext. 3589Fax +86 411-83622844Email fujuan@firsthosp-dmu.comBackground: Bladder urothelial carcinoma (BLCA) is one of the most lethal and aggressive malignancies of genitourinary system that affects human health. The urokinase plasminogen activator receptor (PLAUR) plays essential roles in tumorigenesis and immune modulation, and its aberrant expression is closely correlated with cancer progression. However, whether PLAUR has the potential to be one promising biomarker or immunotherapy target for BLCA is unknown.Methodology: Various online databases were applied to assess the expression profile and prognostic value of PLAUR, as well as its correlation with immune infiltration in BLCA, including Oncomine, PrognoScan, TCGA, cBioPortal, TIMER, TISIDB, UALCAN, and MethSurv. The expression of PLAUR in BLCA was confirmed with ELISA assay for serum samples and immunohistochemistry for tissue samples.Results: The results showed that the expression of PLAUR was elevated in BLCA, which was further confirmed by ELISA and immunohistochemistry. Patients with higher PLAUR level were predicted to have lower overall survival and disease specific survival rates, which were not impacted by the genetic alterations of PLAUR. In addition, the expression of PLAUR was positively associated with immune infiltration, and also the expression levels of gene markers of various immune cells. The negative correlation between PLAUR expression and PLAUR methylation level was observed, among which PLAUR expression was positively correlated with the abundance of 28 kinds of tumor-infiltrating lymphocytes, while PLAUR methylation level was negatively correlated with the abundance of 11 types of tumor-infiltrating lymphocytes. Moreover, the methylation level of PLAUR was closely correlated with patients’ clinicopathological features, and hypomethylation of PLAUR was associated with better outcomes of BLCA patients.Conclusion: These findings suggested that PLAUR had the potential to serve as a valuable detection and prognostic biomarker or immunotherapeutic target for BLCA.Keywords: bladder urothelial carcinoma, PLAUR, biomarker, prognosis, immune infiltration, DNA methylation